Memahami Persepsi Nilai Utilitas Konsumen dan Dampaknya Terhadap Intensi Penggunaan Hashtag Dalam Kampanye Public Relations - Ekta Janarti Chandrasmurti Premadi Suryanto; Kurnia (Jayapangus Press, 2023)
Public relations campaign not only focusing on using the media, but focus on creative approaching to packing communication strategy through the social media content. In this research, specifically discussed about local brand skincare with campaign that use hashtag and utilitarian value. This research aim to understand perception of utilitarian value to intention to use hashtag public relations campaign with survey on local skincare namely NPure. Methodology that were used in this research are quantitative with purposive sampling as the technique. Population in this research are NPure consumers and set the criteria which are social media active user, following NPure social media account, and know about Npure hashtag. Be appointed 100 respondents as a represent sample. Research data are collected with online survey and analyzed using SmartPLS 3.0. Result of this research pointing that utilitarian value take positive effect to intention to use hashtag. According to the result, then NPure as a local skincare brand can use campaign #GenerasiKulitSehat and #NPure as a movement that can consistency used as in accordance influence of utilitarian value that were used by its consumers.